Wisdom From The Ancients - Litfin, Bryan M (Eugene, Oregon : Harvest House Publishers, 2022)
"In Wisdom from the Ancients, author and scholar Bryan Liftin brings you a vivid and readable portrait of the first five centuries of the Christian church, packed with fascinating historical information as well as with applications and insights for believers living today"--
Keywords: Ancients